Analyzing Parametric Sensitivity on the Cyclic Behavior of Steel Shear Walls - Seyed Mohamad Seyed Kolbadi; Nemat Hassani; Seyed Mahdi Seyed-Kolbadi; Masoud Mirtaheri (Shock and Vibration)
As a destructive phenomenon in most parts of the world, earthquake has threatened the safety of structures and the lives of its inhabitants and is considered as the main problem in the seismic vulnerability of buildings. Steel shear walls are regarded as one of the newest structural systems resistant to lateral load in steel structures. The present study aimed to investigate the impact of effective parameters on cyclic behavior by numerically modeling a steel shear wall and comparing it with laboratory results. The results indicated the significant contribution of the thickness of steel shear sheet so that when the thickness changes to 25%, the final response of the structure increased by approximately 20% and decreased by 15%.